Credit programme, women's autonomy a reproductive behaviour evidence from BRAC villages, Bangladesh - Hadi, Abdullahel; Nath, Samir R; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
This paper investigates the role of women's autonomy on their acceptance of contraceptive method in 87 BRAC villages in Manikganj district of Bangladesh. Data for this study were obtained from 1995 sample survey of married women of reproductive age in these villages. Findings reveal that women's autonomy, as measured by the extent to which she believes that the wife should have a decision-making role in five different areas of family life, is positively associated with contraceptive use. While socioeconomic differentials in the acceptance of contraceptive are noticeable in terms of age, number of children ever born, years of schooling. exposure to mass media. land size and occupation of husband, the contraceptive practice among women involved in credit programme is found significantly higher than those not similarly involved. The multivmiate analysis reveals that participation in credit programmes is positively associated with women's empowerment when socioeconomic differentials are taken into account On the other hand, women having high autonomy score are nearly 36 percent more likely to use contraceptives (p<.OS) than those having low autonomy score, controlling for age and number of children ever born of the women. When other factors such as involvement in credit programme. years of schooling. household ownership of land. occupation of husband and exposure to mass media are systematically added to the regression equation, the influence of women's autonomy on contraceptive usc remains high with the same level of significance. The paper concludes that credit-based income generating programme has the potential to bring a significant change in reproductive behaviour of women through increased autonomy.